MINERAL CONTENT AND PHYSICO-CHEMICAL CHARACTERISTICS IN - Syamsul Qadar (Hasanuddin University, 2016)
OES. Characteristic moisture content, ash content, electrical conductivity and pH are also performed. The Largest mineral content of honey is K up to 113,74 mg/L followed by Ca, Mg dan Na (mg/L), respectively 80,68; 28,37; 17,1. Some micro mineral found in Terasa’s honey such as; Fe, Se, Ni, V and Co (mg/L), respectively 0,976; 0,078; 0,11; 0,042; dan 0,035. Heavy metal Cd is also present in very small concentrations average 0,005 mg/LKeyword; multifloral honey, mineral content, moisture content, ash content, conductivity, pH